2014
DOI: 10.17126/joralres.2014.029
|View full text |Cite
|
Sign up to set email alerts
|

Empathetic Orientation in Dentistry students from Latin America. Literature review.

Abstract: Empathy, defined as 'the capacity to relate to someone else's perspective or mental state', has a strong impact on the physician-patient relationship and has the potential to improve the quality of health care. The Jefferson Scale of Empathy (JSE) measures empathy in terms of quantity. It was created to assist medical students, physicians, and people related to health care in general and it has been validated into Spanish showing adequate psychometric properties. The concern for empathy in dentistry students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
3
11
0
7
Order By: Relevance
“…The values of R2 = 14.9% estimated in this research is evidence of the little variability that empathy, the course and gender factors and the latter explain very little about such variation; a result consistent with those of other studies [28]. Most studies do not take this latter statistician into consideration (R2) when empathy is studied within a given population.…”
Section: General Empathysupporting
confidence: 86%
“…The values of R2 = 14.9% estimated in this research is evidence of the little variability that empathy, the course and gender factors and the latter explain very little about such variation; a result consistent with those of other studies [28]. Most studies do not take this latter statistician into consideration (R2) when empathy is studied within a given population.…”
Section: General Empathysupporting
confidence: 86%
“…[40] in Argentina. All these results show that there is variability in the answer of empathy levels in both students outside and inside from all the different universities considered in this study [41]. The totality of authors previously mentioned developed their research in LA with the Jefferson Scale of Empathy (JSE), adapted to the health area researched, therefore, the difference of tools seems not to be the variability source and they can be compared not only by the scale used, but by the same methodological conceptions and statistics with which these studies were developed.…”
Section: Discussionmentioning
confidence: 60%
“…Vera [41], analyzing some of these studies about empathy in dental students from LA, sets three generalizations: 1) the empathy represents a variable behavior; 2) there is a tendency to show higher levels of empathy in female and in higher courses and 3)these variables do not explain more than 20% of the variation found. The authors from this study completely agree with the generalization 1) and 3), but the data observed in this current study shows variability in the gender and, therefore, it is not possible to coincide with the generalization 2), in relation to the "gender" factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigations have found that the "school year" factor has low R 2 values (from 0.02 to 0.06); this means that this factor may only explain 2-6% of the total variation in the empathy outcome measure. [21][22][23] Based on this empirical evidence: a) cross-sectional studies about empathy, considering the school year factor, may be valid to analyze empathic erosion and b) in agreement with some authors, empathy should be studied exploring several factors 3,11,16,17,24 and, from the causality standpoint, it has an alternative-contributory nature. 25 These results show that there is variability in the overall empathic response and its components over the school years and do not fit completely into the erosion model proposed by Hojat et al 13 Our objective was not to deny the model of empathic erosion but to establish that this may be considered a specific element of several different models of distribution of the means in the school year factor.…”
Section: Discussionmentioning
confidence: 84%